Predictive fault-tolerant control for a battery assembly system. Issue 21 (2015) - Seybold, Lothar; Witczak, Marcin; Majdzik, Paweł; Stetter, Ralf
Abstract: The paper deals with modeling and fault-tolerant control of the real battery assembly system, which is under implementation in the RAFI GmbH Company (one of the leading electronic manufacturing service provider in Germany). To model the controlled battery assembly system a unified max-plus algebra and model predictive control framework is employed. Subsequently, the control strategy is enhanced with the fault-tolerance features that enhance the overall performance of the production system being considered. In particular, it enables tolerating (up to some degree) mobile robot and production fault. The paper discusses also the robustness issues, which are inevitable in real production systems. Finally, the last part of the paper shows illustrative examples, which clearly exhibit the performance of the proposed approach.